2015
DOI: 10.1080/19443994.2015.1095120
|View full text |Cite
|
Sign up to set email alerts
|

Removal of fluoride and turbidity from semiconductor industry wastewater by combined coagulation and electroflotation

Abstract: A B S T R A C TReduction of toxic dissolved fluoride and CaF 2 nanoparticle pollution is a critical environmental problem for the semiconductor industry. In this study, suspended matter and fluoride are simultaneously eliminated by combining coagulation and electroflotation. The EF cell was equipped with DSA titanium coated with ruthenium oxide (Ti/RuO 2 ) as anode and stainless steel as cathode. High turbidity removal efficiency is achieved by using EF as a separation technique. The effect of the following pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In order to meet this limitation, different techniques have been used to reduce fluoride concentration, such as electrodialysis (Tahaikt et al, 2004), membrane separation (Ndiaye et al, 2005), adsorption (Zuo et al, 2008), coagulation-electroflotation (Aoudj et al, 2016), and electrocoagulation (EC) (Vasudevan and Oturan, 2014;Kim et al, 2016). Recent studies have demonstrated that the EC method is an attractive alternative for water defluoridation (Un et al, 2009;Aoudj et al, 2010;Kim et al, 2016), because the EC method does not require chemical handling, it is easy to perform, and remarkably reduces the sludge volume and the required space (Zhu et al, 2007;Emamjomeh and Sivakumar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet this limitation, different techniques have been used to reduce fluoride concentration, such as electrodialysis (Tahaikt et al, 2004), membrane separation (Ndiaye et al, 2005), adsorption (Zuo et al, 2008), coagulation-electroflotation (Aoudj et al, 2016), and electrocoagulation (EC) (Vasudevan and Oturan, 2014;Kim et al, 2016). Recent studies have demonstrated that the EC method is an attractive alternative for water defluoridation (Un et al, 2009;Aoudj et al, 2010;Kim et al, 2016), because the EC method does not require chemical handling, it is easy to perform, and remarkably reduces the sludge volume and the required space (Zhu et al, 2007;Emamjomeh and Sivakumar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…generation (Daneshvar et al, 2004;Emamjomeh and Sivakumar, 2005;Aoudj et al, 2016). In the current study, to explore the influence of this key operating parameter on water denitrification, several sets of experiments were carried out at for 30 min at three different CDs (1, 2, and 3 mA/cm 2 ).…”
Section: Influence Of Current Density (Cd)mentioning
confidence: 99%
“…In order to verify the effect of the potential value applied in the electrocoagulation process, the following potential values were investigated: 2.0 to 9.0 V. In fact, it is known (Gonçalves et al 2016;Aoudj et al 2016) that increasing the potential implies an increase in the formation of the…”
Section: Efficiency Of Color Removal As a Function Of Applied Potentialmentioning
confidence: 99%